Adjuvant analgesics in pain management - Onal, Selami Ates (Kare Publ, 2006)
The term adjuvant analgesics describes any drug with a primary indication other than pain, but with analgesic properties in some painful conditions. Adjuvant analgesics often are administered as first-line drugs in the treatment of chronic non-malignant pain. The group includes numerous drugs in diverse classes. Some adjuvant analgesics possess analgesic properties in several types of pain, whereas others are specific for neuropathic pain, or nociceptive pain. Antidepressants, anticonvulsants, neuroleptics, antiarrythmics, antihistaminics, NMDA receptor-antagonists, steroids, muscle relaxants, bisphosphonates, and radiopharmaceuticals are adjuvant agents. This article reviews the evidence supporting the use of adjuvant analgesics for the treatment of pain and emphasizes medical dosages, side effects, and drug interactions.
Analjezik adjuvanlar
Keywords: Adjuvant; analgesic; pain management